A real-world pharmacovigilance analysis of potential ototoxicity associated with sacubitril/valsartan based on FDA Adverse Event Reporting System (FAERS) - Ning Wang; Haijun Wang; Ying Chen; Yanfeng Wang (Scientific Reports)
Abstract Sacubitril/valsartan, a first-in-class angiotensin receptor neprilysin inhibitor, is widely used to treat heart failure. Despite its efficacy, sacubitril/valsartan inevitably causes adverse events such as hypotension, renal dysfunction, hyperkalemia, and angioedema. Sacubitril/valsartan-associated ototoxicity is often underreported in clinical studies and real-world settings. This study aimed to systematically characterize ototoxicity profiles using post-marketing data. Disproportionality analysis was performed using the Food and Drug Administration Adverse Event Reporting System (FAERS) database from 2015 to 2023. The reporting odds ratio (ROR) and information components (IC) were used to detect potential ototoxicity associated with sacubitril/valsartan. Significant signals were defined as ROR025 > 1 and IC025 > 0 in at least three reports. From 272,790 reports on sacubitril/valsartan and 10,798 (4.0%) reports on ototoxicity, sacubitril/valsartan and ototoxicity showed significant association (IC025 = 1.57; ROR025 = 2.99). Dizziness, hypoacusis, balance disorder, and deafness were detected as positive signals; hypoacusis was the strongest (IC025 = 3.21; ROR025 = 9.29). Median time to onset was 45 (10–99) days, and 62.4% of ototoxicity events occurred within 90 days of sacubitril/valsartan administration. Hospitalization accounted for 32.5% of ototoxic outcomes, while life-threatening events, death, and disabling accounted for only 3.9%, 3.4%, and 2.0%, respectively. Sacubitril/valsartan treatment increased ototoxicity risks. Therefore, promptly identifying and treating sacubitril/valsartan-related ototoxicity is critical.